Powers of the prosecutor at implementation of supervision of observance of laws at execution of the punishments which have not been connected with imprisonment - Прищепа, В. І. (Theory and practice of jurisprudence, 2016)
Powers of the prosecutor are considered at implementation of supervision of observance of laws at execution of the criminal punishments which have not been connected with imprisonment. The legal nature of these powers is defined and their system is formulated. Characteristic signs of powers of the prosecutor reveal at implementation of this supervision. Gaps and shortcomings of their legislative regulation and practical realization are revealed, offers on their elimination are provided